Generalized actinomycosis of the pelvic organs. Clinical case - A. V. Kazakova; O. I. Lineva; A. A. Trupakova; I. S. Kiyashko; L. V. Kuznetsova; V. A. Petyanova (IRBIS LLC, 2022)
Here, a clinical case of generalized actinomycosis of the pelvic organs occuring very rarely usually observed in immunocompromised patients is presented. Patient T. referred to the women's clinic with complaints of prolonged genital discharge, itching, burning, and occasional sub-fever. The patient had a history of prolonged hormonal immunosuppressive therapy. After a thorough examination, the patient was consulted by two oncologists. Preliminary diagnosis: suspicio cancer coli; suspicio cancer vaginae. In order to clarify the diagnosis, an in-hospital multifocal scalpel biopsy was performed. The biological material obtained was sent out for intravital pathological and anatomical examination; no signs of malignancy were found. To prevent complications during surgery, the patient underwent separate diagnostic scraping of the uterine cavity and cervical canal after repeated sanitation of the vagina and additional patient examination; hysteroscopy; vulval biopsy; colpocentesis. The final diagnosis was made after obtaining the results of in-surgery microbial culture on nutrient media. Active growth of actinomycetes was detected in the material obtained. The final clinical diagnosis was pelvic actinomycosis, generalized form. Patient T was discharged in satisfactory condition after antibacterial treatment according to the diagnosis for further under gynecologist observation at the women's clinic.